MitoQ protects against high glucose-induced brain microvascular endothelial cells injury via the Nrf2/HO-1 pathway - Min-yan Yang; Zhen Fan; Zhao Zhang; Jin Fan (Elsevier, 2021)
Brain microvascular endothelial cells (BMECs) dysfunction is related to the pathogenesis of neurovascular complication of diabetes mellitus that adversely lead to various CNS disorders. Mitoquinone (MitoQ) is a mitochondria targeted antioxidant that exerts multiple protective effects in many oxidative damage-related diseases. In this study, we determined the protective effects of MitoQ on high glucose (HG)-induced BMECs injury and investigated the underlying mechanism. We found that HG significantly reduced the expression of Nrf2 and HO-1, decreased mitochondrial membrane potential, increased intracellular and mitochondrial reactive oxygen species (ROS) generation, induced cytoskeletal damage and apoptosis in BMECs. In addition, Mito tempol, a mitochondrial ROS scavenger, significantly reduced HG-induced mitochondrial ROS production and attenuated cytoskeletal damage and cell apoptosis, suggesting MtROS production was involved in HG-induced BMECs injury. Moreover, we found that MitoQ treatment significantly upregulated the expression of Nrf2 and HO-1 in HG-induced BMECs, which is accompanied by improved mitochondrial membrane potential and decreased MtROS production. Meanwhile, MitoQ treatment also remarkably attenuated HG-induced cytoskeletal damage and cell apoptosis in BMECs. However, inhibitor of Nrf2 with ML385 impaired the protective effects of MitoQ in HG-induced BMECs. In conclusion, our results suggest that MitoQ exerts protective effect on HG-induced BMECs injury via activating Nrf2/HO-1 pathway.